Low-dose theophylline enhances the anti-inflammatory effects of steroids during exacerbations of COPD. Issue 5 (21st January 2009) - Cosio, B G; Iglesias, A; Rios, A; Noguera, A; Sala, E; Ito, K; Barnes, P J; Agusti, A
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is characterised by an abnormal inflammatory response mainly to cigarette smoke that flares up during exacerbations of the disease (ECOPD). Reduced activity of histone deacetylases (HDAC) contributes to enhanced inflammation in stable COPD. It was hypothesised that HDAC activity is further reduced during ECOPD and that theophylline, an HDAC activator, potentiates the anti-inflammatory effect of steroids in these patients. A study was performed to investigate HDAC activity during ECOPD and the effects of theophylline on the anti-inflammatory effects of steroids in a randomised single-blind controlled study. Methods: 35 patients hospitalised with ECOPD and treated according to international guidelines (including systemic steroids) were randomised to receive or not to receive low-dose oral theophylline (100 mg twice daily). Before treatment and 3 months after discharge, HDAC and nuclear factor-κB (NF-κB) activity in sputum macrophages, the concentration of nitric oxide in exhaled air (eNO) and total antioxidant status (TAS), tumour necrosis factor α (TNFα), interleukin (IL)-6 and IL8 levels in sputum supernatants were measured. Results: Patients receiving standard therapy showed decreased NF-κB activity, eNO concentration and sputum levels of TNFα, IL6 and IL8, as well as increased TAS during recovery of ECOPD, but HDAC activity did not change. The addition of low-dose theophylline increased HDAC activity and further reduced IL8 and TNFα concentrations. Conclusions: During ECOPD, low-dose theophylline increases HDAC activity and improves the anti-inflammatory effects of steroids. Trial registration number: NCT00671151